2021
DOI: 10.2139/ssrn.3769978
|View full text |Cite
|
Sign up to set email alerts
|

More than 50 Long-Term Effects of COVID-19: A Systematic Review and Meta-Analysis

Abstract: Background. COVID-19, caused by SARS-CoV-2, can involve sequelae and other medical complications that last weeks to months after initial recovery, which has come to be called Long-COVID or COVID long-haulers. This systematic review and meta-analysis aims to identify studies assessing longterm effects of COVID-19 and estimates the prevalence of each symptom, sign, or laboratory parameter of patients at a post-COVID-19 stage. Methods. LitCOVID (PubMed and Medline) and Embase were searched by two independent rese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
84
0
8

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(113 citation statements)
references
References 27 publications
2
84
0
8
Order By: Relevance
“…In the last months, an increasing number of studies assessing the presence of post-COVID-19 symptoms have been published. In fact, a meta-analysis has been recently published as a preprint [6] . This meta-analysis found that 80% of COVID-19 survivors exhibited at least one post-COVID-19 symptom, being fatigue (58%), headache (44%), attention disorders (27%), hair loss (25%), and dyspnea (24%) the most frequent [6] .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the last months, an increasing number of studies assessing the presence of post-COVID-19 symptoms have been published. In fact, a meta-analysis has been recently published as a preprint [6] . This meta-analysis found that 80% of COVID-19 survivors exhibited at least one post-COVID-19 symptom, being fatigue (58%), headache (44%), attention disorders (27%), hair loss (25%), and dyspnea (24%) the most frequent [6] .…”
Section: Introductionmentioning
confidence: 99%
“…In fact, a meta-analysis has been recently published as a preprint [6] . This meta-analysis found that 80% of COVID-19 survivors exhibited at least one post-COVID-19 symptom, being fatigue (58%), headache (44%), attention disorders (27%), hair loss (25%), and dyspnea (24%) the most frequent [6] . However, this review pooled prevalence rates without considering follow-up periods after symptoms and did not differentiate between hospitalized and non-hospitalized patients [6] .…”
Section: Introductionmentioning
confidence: 99%
“…The ten most frequent individual symptoms at 30-and 90 days post-discharge were fatigue, headache, sadness, alopecia, insomnia, desire to cry, anguish, anger, anhedonia, and back pain, which are similar to those described in previous reports. 5,11,15,19 Most recently, a study on the attributes and predictors of long COVID-19 also reported similar individual symptoms (i.e., fatigue, headache, dyspnoea, and anosmia) that persisted for 12 weeks. 3 Although symptoms like fatigue, cough, and chest pain decreased over time in our study, patients who were discharged from the TCH reported higher frequencies of alopecia, rhinorrhoea, lacrimation, lack of concentration, paraesthesia, arthralgia, and memory loss at 90 days compared with 30 days.…”
Section: Discussionmentioning
confidence: 88%
“…A severe and often lethal immunoreaction can occur from respiratory and other infection sites, termed a "cytokine storm" (C. Chen, Zhang, Ju, & He, 2020). Even after acute SARS-CoV-2 infection has passed, individuals can suffer a suite of complications for many months, termed "Long Haul" syndrome (López-León et al, 2021), and the causes of these syndromes are not well understood.…”
Section: Introductionmentioning
confidence: 99%